Safeguards Assessments-2008 Update. (Policy Papers; Policy Paper ;, 2008)
Safeguards Activities. In the year to June 30, 2008, 10 safeguards assessments were conducted bringing the total number of assessments completed since 2000 to 122. At year-end, 72 central banks were subject to ongoing safeguards monitoring. Assessment activity has also included several recent high-profile cases of misreporting or misuse, along with intensive analysis of special audit reports initiated in such cases. In the latter part of 2008, staff developed modalities for expedited safeguards assessments under the Emergency Financing Mechanism.